2022
DOI: 10.1093/ehjacc/zuac114
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and associated clinical outcomes of low cardiac output syndrome following cardiac surgery: insights from the LEVO-CTS trial

Abstract: Background High-risk cardiac surgery is commonly complicated by low cardiac output syndrome (LCOS) which is associated with high mortality. There are limited data derived from multi-center studies with adjudicated endpoints describing factors associated with LCOS and its downstream clinical outcomes. Methods The Levosimendan in Patients with Left Ventricular Systolic Dysfunction Undergoing Cardiac Surgery Requiring Cardiopulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Independent predictors of increased mortality in patients with LCOS were renal failure (OR 4.3), patient age (OR 1.03) and the need for a reoperative surgical intervention (OR 1.8) [ 51 ]. Further studies should be carried out on the utility of both pre and postoperative hyperuricemia in predicting LCOS, as there is evidence that adjusting the type of cardiac surgery procedure and using inotropes such as levosimendan postoperatively significantly reduce the risk of postoperative LCOS [ 52 ]. Recognizing the patients at risk of this major cardiac surgery complication before the procedure itself or immediately after using a single noninvasive blood biomarker (UA) would have the potential to significantly reduce in-hospital mortality, hospitalization costs, and complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Independent predictors of increased mortality in patients with LCOS were renal failure (OR 4.3), patient age (OR 1.03) and the need for a reoperative surgical intervention (OR 1.8) [ 51 ]. Further studies should be carried out on the utility of both pre and postoperative hyperuricemia in predicting LCOS, as there is evidence that adjusting the type of cardiac surgery procedure and using inotropes such as levosimendan postoperatively significantly reduce the risk of postoperative LCOS [ 52 ]. Recognizing the patients at risk of this major cardiac surgery complication before the procedure itself or immediately after using a single noninvasive blood biomarker (UA) would have the potential to significantly reduce in-hospital mortality, hospitalization costs, and complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical myocardial revascularization in patients with low ejection fraction carries a significant risk of perioperative mortality and morbidity related to the development of postcardiotomy cardiogenic shock [7 ▪▪ ,8]. Below, we list some medical and temporary mechanical support options that may be considered in the perioperative period.…”
Section: Preoperative Optimization and Risk Mitigationmentioning
confidence: 99%
“…Coronary artery bypass grafting for patients with severely reduced cardiac function is challenging because of the high incidence of postoperative low cardiac output syndrome [1]. A study that investigated 55,515 patients in New York State database reported that patients with low ejection fraction had >4 times higher mortality than patients with high ejection fraction [2].…”
Section: Introductionmentioning
confidence: 99%